Electroactive Phenolic Contributors and Antioxidant Capacity of Flesh and Peel of 11 Apple Cultivars Measured by Cyclic Voltammetry and HPLC-DAD-MS/MS - Danuta Zielińska; Marcin Turemko (MDPI AG, 2020)
In this study, 11 apple cultivars were characterized by their total phenolic content (TPC) and total flavonoid content (TFC) and antioxidant, reducing, and chelating capacity by 2,2-diphenyl-1-picrylhydrazyl (DPPH) test, cyclic voltammetry (CV), and ferric reducing antioxidant power (FRAP) assays; and ferrous ion chelating capacity. The phenolic compounds in flesh and peel were determined by liquid chromatography coupled to mass spectrometry and diode array detector (HPLC-DAD-MS/MS) and their electroactivity by CV. The results showed higher TPC, TFC, and antioxidant capacity by DPPH test in the peels of all apple cultivars as compared to the respective flesh. The peel extracts also showed two-fold higher FRAP values as compared to the flesh extracts. The reducing capacity of the peel and flesh determined by CV measurements confirmed the results achieved by spectrophotometric methods of evaluating antioxidant capacity. There was no significant difference in chelating capacity in the peel and flesh. The HPLC-DAD-MS/MS analysis showed the presence of 11 phenolic compounds in the peel and flesh which varied in antioxidant, reducing, and chelating activity. The order of the phenolic compound content in flesh and peel in Quinte cultivar, which showed the highest antioxidant capacity, was as follows: epicatechin > chlorogenic acid > quercetin 3-arabinoside > quercetin 3-glucoside > cyanidin 3-galactoside > quercetin 3-rhamnoside > catechin > phloridzin > rutin > phloretin = quercetin. CV results were highly correlated with those obtained by spectrophotometry and HPLC-DAD-MS/MS, providing evidence to support the use of cyclic voltammetry as a rapid method to determine the phenolic profile and reducing the power of apple flesh and peel. The association between antioxidant assays and phenolic compound content showed that the highest contribution to the antioxidant capacity of apple peel and flesh was provided by catechin, epicatechin, and cyadinin-3-galactoside, while phloretin, phloridzin, and chlorogenic acid were the main contributors to chelating activity. Results from this study clearly indicate that removing the peel from apples may induce a significant loss of antioxidants.